2010
DOI: 10.1017/s0033291710001121
|View full text |Cite
|
Sign up to set email alerts
|

Memory performance in acute and weight-restored anorexia nervosa patients

Abstract: The findings suggest that impaired memory performance is either a stable trait characteristic or a scar effect of chronic starvation that may play a role in the development and/or persistence of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 61 publications
6
55
3
Order By: Relevance
“…The cognitive measures in this study were selected because of their known relationship to the thalamo-frontal circuits under study; however, they have limitations. Although we found that working memory, as measured by the LNS, was significantly impaired in patients with AN in our study, other studies have not found impairment in this cognitive domain (Lao-Kaim et al, 2014;Nikendei et al, 2011). Cognitive flexibility is often impaired in AN (Steinglass et al, 2006;Wu et al, 2014), but findings with the Stroop and TMT have been inconsistent, perhaps because these tasks are less cognitively demanding.…”
Section: Discussioncontrasting
confidence: 91%
“…The cognitive measures in this study were selected because of their known relationship to the thalamo-frontal circuits under study; however, they have limitations. Although we found that working memory, as measured by the LNS, was significantly impaired in patients with AN in our study, other studies have not found impairment in this cognitive domain (Lao-Kaim et al, 2014;Nikendei et al, 2011). Cognitive flexibility is often impaired in AN (Steinglass et al, 2006;Wu et al, 2014), but findings with the Stroop and TMT have been inconsistent, perhaps because these tasks are less cognitively demanding.…”
Section: Discussioncontrasting
confidence: 91%
“…With regards to vWM and in accordance with the current study, a recent neuropsychological assessment found no difference on isolated backwards digit scores between restricting, binge-purging, weight-gained AN subtypes and HC [48]. Others have found slower performance on a memory scanning task requiring a response to pre-specified numbers when they appear within a sequence [57] and conversely, two recent studies have reported superior vWM performance in AN.…”
Section: Discussionsupporting
confidence: 88%
“…People with AN exhibit inefficient visuo-spatial memory and processing [36], cognitive flexibility [63], long-term memory [48], attention [17] and central coherence [38]. However, the results of studies assessing verbal working memory (vWM) in AN have been inconsistent (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Some participants had a normal BMI (N17) because they were on a relapse of symptomatology at the time of assessment and, thus, they still met the inclusion criteria for the study given that the anorexia nervosa diagnosis was made by an eating disorder specialist based on information other than the BMI (Stedal, Rose, Frampton, Landro, & Lask, 2012). Recent research showed no differences in immediate and delayed recall between underweight and normal-weight patients with AN, whereas both groups scored significantly lower than healthy controls (Nikendei et al, 2011).…”
Section: Methodsmentioning
confidence: 99%